Peritoneal Dialysis-Related Peritonitis Due to Staphylococcus aureus: A Single-Center Experience over 15 Years - Barretti, Pasqual [UNESP]; Moraes, Taise M. C. [UNESP]; Camargo, Carlos H. [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Mondelli, Alessandro Lia [UNESP]; Montelli, Augusto C. [UNESP]; Cunha, Maria de Lourdes Ribeiro de Souza da [UNESP] (Public Library Science, 2012)
Peritonitis caused by Staphylococcus aureus is a serious complication of peritoneal dialysis (PD), which is associated with poor outcome and high PD failure rates. We reviewed the records of 62 S. aureus peritonitis episodes that occurred between 1996 and 2010 in the dialysis unit of a single university hospital and evaluated the host and bacterial factors influencing peritonitis outcome. Peritonitis incidence was calculated for three subsequent 5-year periods and compared using a Poisson regression model. The production of biofilm, enzymes, and toxins was evaluated. Oxacillin resistance was evaluated based on minimum inhibitory concentration and presence of the mecA gene. Logistic regression was used for the analysis of demographic, clinical, and microbiological factors influencing peritonitis outcome. Resolution and death rates were compared with 117 contemporary coagulase-negative staphylococcus (CoNS) episodes. The incidence of S. aureus peritonitis declined significantly over time from 0.13 in 1996-2000 to 0.04 episodes/patient/year in 2006-2010 (p = 0.03). The oxacillin resistance rate was 11.3%. Toxin and enzyme production was expressive, except for enterotoxin D. Biofilm production was positive in 88.7% of strains. The presence of the mecA gene was associated with a higher frequency of fever and abdominal pain. The logistic regression model showed that diabetes mellitus (p = 0.009) and beta-hemolysin production (p = 0.006) were independent predictors of non-resolution of infection. The probability of resolution was higher among patients aged 41 to 60 years than among those >60 years (p = 0.02). A trend to higher death rate was observed for S. aureus episodes (9.7%) compared to CoNS episodes (2.5%), (p = 0.08), whereas resolution rates were similar. Despite the decline in incidence, S. aureus peritonitis remains a serious complication of PD that is associated with a high death rate. The outcome of this infection is negatively influenced by host factors such as age and diabetes mellitus. In addition, beta-hemolysin production is predictive of non-resolution of infection, suggesting a pathogenic role of this factor in PD-related S. aureus peritonitis.